DOI: 10.26512/2014.11.d.17735
|View full text |Cite
|
Sign up to set email alerts
|

Remoção de microesferas de poliestireno, em substituição a oocitos de Crypstosporidium, por filtração direta ascendente no tratamento de água usando o coagulante quitosana

Abstract: A Deus por ter me concedido a vida, a saúde, a inteligência e a força para suportar as adversidades e concluir este trabalho, por me enviar aos seus melhores anjos para me cuidar, por ter me permitido nascer no paraíso, na Colômbia, pela experiência vivida aqui no Brasil, pelas alegrias e tristezas, por todas as benções. Às pessoas que me acolheram, que se tomaram um tempo para me conhecer e trocar histórias, e que fizeram a minha permanência neste lugar mais amena e feliz, obrigada pelo seu apoio e alegria. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…As can be seen in Table 5 and Figure 2, the average residual turbidity remained consistently below 0.32 NTU in all experiments, a value that is below the limits established for filtered water by the Brazilian drinking water guidelines, less than or equal to 0.5 NTU in 95% of measurements [15]. Similar results were reported by Fagundes [26], Fernandes [27], Nascimento [28], and Méndez [29], authors who conducted their studies using raw water from the same source (Paranoá Lake) and similar filters. With turbidity values less than or equal to 0.3 NTU in 95% of measurements of filtered water, at least a 2.5 log removal of Cryptosporidium can be obtained in direct filtration plants [7,16].…”
Section: Turbidity and Head Loss Developmentsupporting
confidence: 85%
“…As can be seen in Table 5 and Figure 2, the average residual turbidity remained consistently below 0.32 NTU in all experiments, a value that is below the limits established for filtered water by the Brazilian drinking water guidelines, less than or equal to 0.5 NTU in 95% of measurements [15]. Similar results were reported by Fagundes [26], Fernandes [27], Nascimento [28], and Méndez [29], authors who conducted their studies using raw water from the same source (Paranoá Lake) and similar filters. With turbidity values less than or equal to 0.3 NTU in 95% of measurements of filtered water, at least a 2.5 log removal of Cryptosporidium can be obtained in direct filtration plants [7,16].…”
Section: Turbidity and Head Loss Developmentsupporting
confidence: 85%
“…The difference in the total particle counts in raw water was mainly due to the increase in the number of particles in the ranges 8-15 and 20-70 µm. This behavior is associated with the particle size distribution of the kaolinite suspension added to the water, whose granulometric analysis revealed that nearly 70% of kaolinite particles were greater than 7 µm [36].…”
Section: Particle Counts and Cryptosporidium Oocystsmentioning
confidence: 95%